Improvement of Vocational Skills of SMK Muhammadiyah Rappang Students Through an Entrepreneurship-Based Training Program in Pancarijang District, Sidenreng Rappang Regency - Sam Hermansyah; Syamsu T; Syamsunir; Winda Pratiwi, Khaeruninisa; Hamka, Nurhikmah; Ramli, Rusdi (Unram Journal of Community Service, 2025)
This study aims to improve students' entrepreneurial skills at SMK Muhammadiyah Rappang through an entrepreneurship-based training program in Pancarijang District, Sidenreng Rappang Regency. Amid the challenges of globalization and technological advancements, SMK Muhammadiyah Rappang faces mismatched competencies between what is taught and the job market's needs. Many students come from economically disadvantaged backgrounds and have limited access to relevant entrepreneurial training. This training program is designed to address challenges in production and marketing by providing the necessary skills to create quality products and market them using digital technology. The methods used in this research include initial needs assessment, product innovation training, and digital marketing and branding training. The program also provides guidance on implementing the marketing and production strategies taught. The results of this training show improved students' skills in product innovation, more efficient production management, and the ability to market products online through social media and e-commerce platforms. The discussion highlights that, although challenges in production and marketing still exist, the use of appropriate technology and an understanding of digital marketing can enhance the competitiveness of local products. This program provides students with entrepreneurial skills and empowers the local community to become independent and innovative entrepreneurs. The success of this program is expected to create new job opportunities and strengthen the local economy in Sidenreng Rappang Regency.